STUDY OF REGIONAL COMPETITIVENESS IN CENTRAL SULAWESI - Suparman, Suparman (LPPM STIE Muhammadiah Bandung, 2021)
This research aims for measure the regional competitiveness in Central Sulawesi Province. The analysis method used is algorithm models developed by Asia Competitiveness Institute (ACI) by using 4 scopes, those are; Macro Economy Stability; Government and Institution Planning; Financial Condition, Business and Labor; Life Quality and Infrastructural Development. The result discovers the index of regency/city in Central Sulawesi Province that is Banggai regency 3.6763, Palu city 3.4010, and Morowali regency 3.2672, as the regions which have the high competitiveness ability in Central Sulawesi, while some of regions which has a low competitiveness ability are Tojo Una-Una regency, Banggai Laut regency, Sigi, and Banggai Kepulauan regency.